1983
DOI: 10.1161/01.res.53.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Myosin isoenzymes in normal and hypertrophied human ventricular myocardium.

Abstract: We tested the hypothesis that hypertrophy of the human heart is associated with the redistribution of ventricular isomyosins. Human cardiac myosin was isolated from autopsy samples of left ventricular free wall of patients with cardiac hypertrophy and of fetal, young, and adult subjects without heart disease. The following parameters were studied: electrophoretic migration in denaturing and non-denaturing conditions; immunological cross-reactivities with three different types of antibodies; and early phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
102
2
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(108 citation statements)
references
References 54 publications
3
102
2
1
Order By: Relevance
“…It is noted that an important change in the phenotype of the hypertrophied heart is the transition of the expression of myosin heavy chain (MHC) gene expression. Under physiological conditions, α-MHC, which promotes faster shortening velocity of cardiac myofibres due to high ATPase activity, is predominant (38,42). On the other hand, in HF, there is a downregulation of α-MHC and upregulation of β-MHC, which is expressed in fetal genes, with less ATPase activity (39,40,41,42).…”
Section: Ros and Cardiac Hypertrophy Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that an important change in the phenotype of the hypertrophied heart is the transition of the expression of myosin heavy chain (MHC) gene expression. Under physiological conditions, α-MHC, which promotes faster shortening velocity of cardiac myofibres due to high ATPase activity, is predominant (38,42). On the other hand, in HF, there is a downregulation of α-MHC and upregulation of β-MHC, which is expressed in fetal genes, with less ATPase activity (39,40,41,42).…”
Section: Ros and Cardiac Hypertrophy Signallingmentioning
confidence: 99%
“…Under physiological conditions, α-MHC, which promotes faster shortening velocity of cardiac myofibres due to high ATPase activity, is predominant (38,42). On the other hand, in HF, there is a downregulation of α-MHC and upregulation of β-MHC, which is expressed in fetal genes, with less ATPase activity (39,40,41,42). It has been shown that there is a correlation between the expression of β-MHC and the degree of cardiac hypertrophy (43).…”
Section: Ros and Cardiac Hypertrophy Signallingmentioning
confidence: 99%
“…Several investigators have reported an increase in β-MHC and a decrease in the α-MHC isoform in the hypertrophied ventricle in rats (31,32) and humans (33), and found that the expression of β-MHC at the mRNA level is closely correlated with the degree of cardiac hypertrophy (31,34). However, during MHC expression, transcriptional activity does not necessarily reflect mRNA or protein levels.…”
Section: Myofibrillar Assembly In Cardiac Hypertrophymentioning
confidence: 99%
“…Upregulation of these fetal protein isoforms is associated with downregulation of the corresponding adult isoforms, α-MHC and α-cardiac actin (96). These molecular processes are correlated with the development of hypertrophy and the thickness of the ventricular wall, which has been shown to result from an increase in cell size due to an increase in the number of sarcomeres and mitochondria within the cell (97).…”
Section: Molecular Basis For Alterations In Myocardial Structure and mentioning
confidence: 99%